Optical conversion of pure spin currents in hybrid molecular devices. Issue 1 (December 2017) - Wheeler, May; Ma'Mari, Fatma; Rogers, Matthew; Gonçalves, Francisco; Moorsom, Timothy; Brataas, Arne; Stamps, Robert; Ali, Mannan; Burnell, Gavin; Hickey, B.; Cespedes, Oscar
Abstract Carbon-based molecules offer unparalleled potential for THz and optical devices controlled by pure spin currents: a low-dissipation flow of electronic spins with no net charge displacement. However, the research so far has been focused on the electrical conversion of the spin imbalance, where molecular materials are used to mimic their crystalline counterparts. Here, we use spin currents to access the molecular dynamics and optical properties of a fullerene layer. The spin mixing conductance across Py/C60 interfaces is increased by 10% (5 × 1018 m−2 ) under optical irradiation. Measurements show up to a 30% higher light absorbance and a factor of 2 larger photoemission during spin pumping. We also observe a 0.15 THz slowdown and a narrowing of the vibrational peaks. The effects are attributed to changes in the non-radiative damping and energy transfer. This opens new research paths in hybrid magneto-molecular optoelectronics, and the optical detection of spin physics in these materials. Carbon-based molecules could prove useful in terahertz and optical devices controlled by pure spin currents. Here, conversely, the authors use spin currents to probe molecular dynamics and enhance the optical response of a fullerene layer, enabling hybrid magneto-molecular optoelectronic devices.